Respiratory morbidities of jute mill workers in Nepal (Health Renaissance, 2012)
Background: Occupational safety, health and working conditions indicate that there are potential risks of health hazards and diseases at workplaces. Jute processing yields dust. Respiratory symptoms are common among workers exposed to high dust area. Objectives: To find out respiratory morbidities among jute mill workers and to compare the rate of peak expiratory flow among jute mill workers. Methods: Cross-sectional study was conducted among 900 workers in jute processing departments of Arihant multi-fibres Ltd., Sonapur, Sunsari, Nepal. Pre-tested semi-structured questionnaire were used. Peak expiratory flow rate (PEFR), height and weight were measured. Proportion, chi-square test and odd ratio were calculated. ANOVA was applied. Results: About 24 % workers belong to 25-29 years of age. Around 21% and 86% workers were smokers and tobacco chewers respectively. Two fifth of workers (41.6%) were working for less than 5 years. Acute upper respiratory infection (14.2%), chronic bronchitis (0.3%), acute lower respiratory infections (0.77%), allergic rhinitis (0.1%) and asthma (0.4%) were the respiratory morbidities among the workers. Chest tightness was found among 7 workers. Difficulty in breathing was found among 26 workers. The PEFR variations were found significant among workers in the low and high dust area and without and with symptom of cough. Association between cough and exposure to dusty area was shown to be statistically significant (p